Effect of Methanolic Extract in Ointment and Powder of Kalanchoe Pinnata (Lamk) Leaf in Ointment towards Incision Wound Healing in Mice - Adi K Suprapto; Fen Tih; Endang Evacuasiany (Universitas Kristen Maranatha, 2015)
Wound is a very common thing that can happen to all people around the world. The purpose of this study is to investigate the effect of methanolic extract and powder of Kalanchoe pinnata (Lamk) leaf in ointment. The methodology is laboratoric experimental design. Six groups of mice (n=30) were incised for 8 mm and treated with different treatment: methanolic extract of Kalanchoe pinnata (Lamk) leaves in ointment (SEMDSB) 10%, SEMDSB 20%, Kalanchoe pinnata (Lamk) leaves powder in ointment (SSDSB) 10%, SSDSB 20%, vaseline album (ointment) as negative control, andÂ povidone iodine ointment as positive control. Examination is carried out by measuring the width of wounds in mice every day until the wound interlocked. Data analysis used one way ANOVA continued by Tukey HSD with Î±=0,05. The result showed the average time for wound healing (in days) are: SEMDSB 10% (7.2), SEMDSB 20% (6.6), SSDSB 10% (8.8), SSDSB 20% (7.6), negative control (10.6), and positive control (7.8). SEMDSB 10%, SEMDSB 20%, and SSDSB 20% showed highly significant difference (p = 0,000) and SSDSB 10% showed significant difference (p=0,021) when compared to negative control. As conclusion, methanolic extractÂ and powder of Kalanchoe pinnata (Lamk) leaves in ointment can accelerate wound healing time.Â Keywords: ointment, Kalanchoe pinnata (Lamk), wound healing, mice